Advanced Computing and Communication Technologies Proceedings of the 11th ICACCT 2018 - Mandal, Jyotsna Kumar; Bhattacharyya, Dhananjay; Auluck, Nitin; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
The book includes papers on a wide range of emerging research topics spanning theory, systems and applications of computing and communication technologies viz. Nonlinear Dynamics in Cryptography, Discrete domain Swarm Robotics, Machine Learning, Facility Layout Problem, Crowdfunding Projects, Deep Learning, MHD Nanofluid Flow, Medical Diagnostics, Human Computer Interface, Social Networking, System Performance, Wireless Sensor Networks, Cognitive Radio Networks, Antenna Design etc.; presented at the 11th International Conference on Advanced Computing and Communications Technologies (11th ICACCT 2018) held on 17-18 February, 2018 at Asia Pacific Institute of Information Technology, Panipat, India.
Part I: Advanced Computing -- Chapter 1: Authentication based on Nonlinear Dynamics -- Chapter 2: Gathering in the Discrete Domain : State-of-the-Art -- Chapter 3: Modified SA Algorithm for Bi-objective Robust Stochastic Cellular Facility Layout in Cellular Manufacturing Systems -- Chapter 4: Fuzzy time series forecasting method using probabilistic fuzzy sets -- Chapter 5: Ohmic-viscous dissipation and heat generation/absorption effects on MHD nanofluid flow over a stretching cylinder with suction/injection -- Chapter 6: Interlocking nodes for structural analysis in social networking -- Chapter 7: A novel construction method of intuitionistic fuzzy set from fuzzy set and its application in multi-criteria decision making problem -- Chapter 8: Design of an Audio Repository for Blind and Visually Impaired : A Case Study -- Chapter 9: A Futuristic Deep Learning Framework approach for Land Use Land Cover Classification using Remote Sensing Imagery -- Chapter 10: Prediction Model for Crowdfunding Projects -- Chapter 11: An Enhanced Approach for Detecting Helmet on Motorcyclists using Image Processing and Machine Learning Techniques -- Chapter 12: Affinity Aware Synchronization in Work Stealing Run-Times for NUMA Multi-Core Processors -- Chapter 13: Backpropagation Neural Network vs Logistic Regression in Heart Disease Classification -- Part II: Communication Technologies -- Chapter 14: Wormhole Attack in Wireless Sensor Networks: A Critical Review -- Chapter 15: A General Framework for Spectrum Assignment in Cognitive Radio Networks -- Chapter 16: Novel Schemes for Energy Efficient IoT -- Chapter 17: Minimizing the total range with two power levels in Wireless Sensor Networks -- Part III: Electronics, Antenna Design -- Chapter 18: Comparative Study of Rectangular and E-Shaped Microstrip Patch Antenna Array for X- Band Applications -- Chapter 19: An Archimedean Spiral Shaped Frequency Selective De-fected Structure for Narrow band High Q Applications -- Chapter 20: Challenge Response Pair (CRP) Generator using Schmitt Trigger Physical Unclonable Function. .
Keywords: Computational intelligence; Artificial intelligence; Telecommunication; Computational Intelligence; Artificial Intelligence; Communications Engineering, Networks